The need for safety in the aspect of psychosocial dissonance and facilitation of social interaction - Veronika V. Vasina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper deals with five levels of motives (needs) of modern students according to the knownA. Maslow model of needs. The safety need psychology is shown to be connected with a psychosocial dissonance as overcoming the arising mental tension and the choice of the development route at the personality level and also with a facilitation of social interaction as influence of the strangers who do not participate in social interaction directly, and social environment influence on the development trajectory choice at the social level. Empirical data are obtained on the basis of a technique "Motivation of educational/professional activity" (V.V. Vasina,R.G. Khalitov). The comparative analysis of students’ safety need is carried out. Psychological interpretation of a low level indicator of safety need is given.